2015
DOI: 10.5204/intjfyhe.v6i1.266
|View full text |Cite
|
Sign up to set email alerts
|

Track and Connect: Enhancing student retention and success at the University of Sydney. A Practice Report

Abstract: In 2012, staff in Student Support Services at The University of Sydney piloted an early intervention program to increase first year student engagement and retention. Founded in best-practice, evidence-based research, the Track and Connect program was developed in response to a study into first year undergraduate student attrition by the University's Planning and Information Office, in consultation with Counselling and Psychological Services. Track and Connect provides tailored advice and support to students id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A further implication evidenced by the improvement in the 2017 CFY cohort's WAM is that holistic, integrated support is more beneficial than a subject-based approach, although any intervention appears to be better than none, including contact via SMS and email. The integrated model described here provides an important point of difference to similar programs used at other universities (Barnes et al, 2015;Nelson et al, 2009;Potter & Parkinson, 2010;Tower, Walker, Wilson, Watson, & Tronoff, 2015), which typically identify and support students on the basis of individual subjects. Even those examining the student experience across multiple subjects typically report their data on an individual subject basis, which we believe may conceal the benefits that come from taking a whole-ofstudent approach to appreciative advising modelled here in the CFY example.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…A further implication evidenced by the improvement in the 2017 CFY cohort's WAM is that holistic, integrated support is more beneficial than a subject-based approach, although any intervention appears to be better than none, including contact via SMS and email. The integrated model described here provides an important point of difference to similar programs used at other universities (Barnes et al, 2015;Nelson et al, 2009;Potter & Parkinson, 2010;Tower, Walker, Wilson, Watson, & Tronoff, 2015), which typically identify and support students on the basis of individual subjects. Even those examining the student experience across multiple subjects typically report their data on an individual subject basis, which we believe may conceal the benefits that come from taking a whole-ofstudent approach to appreciative advising modelled here in the CFY example.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The transfer from the Outer to the Inner Core must be completed successfully within a short time frame as first-year students engage and connect, or conversely, disconnect with their tertiary institution within the first two to six weeks of study (Barnes, Macalpine, & Munro, 2015). These Inner and Outer Cores both currently function at the institution, yet a disconnect of how to best utilise the cores cohesively had been identified in the review of the SOE.…”
Section: Current First-year Transition Process For Soe Studentsmentioning
confidence: 99%
“…So, I will engage in discussion boards and also work to highlight the importance of academic literacy skills  I monitor any emails/posts where students indicate that they are not feeling confident in their ability to do something or unsure about their understanding and I follow-up with those students, usually through Moodle to encourage others to follow suit if they feel the same way What was apparent from the participants" responses was that there was no standard approach available and used within first-year units in relation to early diagnostic assessment, where students who may be ill-prepared to engage with their study were able to be identified at an early stage and provided the support they may require. The importance of the first six weeks of university study after commencement has been identified as a period of high vulnerability for students (Barnes et al, 2015), particularly those from a non-traditional background (P. Whannell, Whannell, & Allen, 2012).…”
Section: Importance At the Institutional Levelmentioning
confidence: 99%
“…Graduating students were trained to be mentors as part of a final year capstone course after which they started attending first tutorials to engage first year students in learning, encourage them to take a reflective approach, and enhance skills in both individual and group-based learning. Another example that utilizes peer-support is the "Track and Connect" program (Barnes et al, 2015). This program depends on the "at-risk trends" identified by faculty, such as a lack of assumed prior knowledge to identify the students who may be struggling in the university.…”
Section: School Of Electrical and Information Engineering The Univermentioning
confidence: 99%